Preliminary phytochemical and in vitro antibacterial evaluation of the crude pericarp extract of Hyphaene thebaica (doumpalm). Issue 1 (2013) - Auwal, M. S.; Mairiga, I. A.; Shuaibu, A.; Ibrahim, A.; Gulani, I. A.; Wampana, B.; Lateefat, G. I.; Lawan, F. A.; Sanda, K. A.; Thaluvwa, A. B.; Njobdi, A. N.; Yagana, K. Z.
No abstract available